Delayed Intervention of Infected Penile Siliconoma due to Unauthorized Hair Oil Injection: A Case Report - Pinem, Joko Syuhada; Pariputra, Yutha (Brawijaya Journal of Urology, 2025)
Introduction. Penile siliconoma is an uncommon condition resulting from silicone injections into the penis, often prompted by the desire to enhance sexual performance or physical appearance. However, these procedures are associated with a significant risk of complications, including infection, granuloma formation, and penile deformation. Case. This case report describes a case of penile siliconoma in an 18-year-old male patient from a rural area who underwent penile silicone injection without medical supervision. The patient presented with thickening of the skin on the penile shaft accompanied by sores and severe pain due to self-injecting hair oil. Surgical procedures by urologists with partial excision, extraction of necrotic tissue, and reconstruction are carried out in the hope of preventing further damage to the penis. Conclusion. The case presented here underscores the critical need for patients to exercise caution and seek medical guidance before undergoing any unauthorized cosmetic procedures, particularly those involving the injection of foreign materials into sensitive areas of the body.